RANCANGAN INFRASTRUKTUR E-BISNIS BUSINESS INTELLIGENCE PADA PERGURUAN TINGGI - Spits Warnars H.L.H (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2008)
In order to compete with others, high education need complete their infrastructure with Information technology support. High level management as a decision maker needs something that can boost the system to compete with other high education. They need IT knowledge that can support them to view the future and can help the whole system to improve their services. Business Intelligence is one of term of Decision Support System which can help the management by something that they can forecast and decide. High Education needs infrastructure design to make good foundation for business intelligent implementation which will be implemented on internet or e-business.